2019
DOI: 10.1097/ajp.0000000000000657
|View full text |Cite
|
Sign up to set email alerts
|

The Magnitude of Offset Analgesia as a Measure of Endogenous Pain Modulation in Healthy Participants and Patients With Chronic Pain

Abstract: Objective: Offset analgesia (OA) is a test paradigm increasingly used to estimate endogenous pain modulation characterized by a disproportionally profound analgesia after a small decrease of a heat stimulus. This systematic review and meta-analysis examined the magnitude and difference of OA in healthy participants and chronic pain patients. Materials and Methods: Controlled trials, case-control studies, cross-sectional studies, case-series or other obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 52 publications
10
52
0
Order By: Relevance
“…This is distinct from the presentation of chronic TMD pain patients, in whom clinical pain affects mostly the jaw and face — even though comorbid pain conditions are relatively common in this population . Clinical and psychosocial characteristics of the chronic TMD cases included in the present study were similar to those reported by the OPPERA case‐control study and to previous studies comparing OA responses in pain patients relative to controls . This similarity reduces the likelihood that clinical and psychosocial characteristics of our sample would suffice to explain the lack of OA response differences between chronic TMD cases and controls.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…This is distinct from the presentation of chronic TMD pain patients, in whom clinical pain affects mostly the jaw and face — even though comorbid pain conditions are relatively common in this population . Clinical and psychosocial characteristics of the chronic TMD cases included in the present study were similar to those reported by the OPPERA case‐control study and to previous studies comparing OA responses in pain patients relative to controls . This similarity reduces the likelihood that clinical and psychosocial characteristics of our sample would suffice to explain the lack of OA response differences between chronic TMD cases and controls.…”
Section: Discussionsupporting
confidence: 63%
“…Delta COVAS for TMD cases (mean ± SD: 53.5 ± 22) and controls (51.6 ± 22.9) were relatively similar to the reported mean for healthy controls of similar age range described by Niesters et al: age 20‐39 years (n = 14): 45.3 ± 7.1; 40‐59 years (n = 23): 51.8 ± 4.5. This further supports that TMD participants present with similar OA response as pain‐free controls when tested over the forearm, the body test site most commonly used to assess OA responses . One study tested OA responses not only over the forearm but also over the thenar eminence of healthy, pain‐free participants and found no significant OA response in the latter, suggesting that OA may be site‐specific.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations